1997
DOI: 10.1007/s004310050632
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in childhood asthma hospitalisations in Finland, 1972-1992

Abstract: A clear seasonal variation could be observed in childhood asthma hospital admissions, together with age and sex-related differences in this seasonality. Preventive treatment for asthma should be used effectively in order to avoid acute attacks leading to hospitalisation in children who are allergic to birch pollen and also at times of viral respiratory infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
3
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 26 publications
(33 reference statements)
7
38
3
2
Order By: Relevance
“…Some studies show no significant difference between males and females [15]. The need for hospital admission was significantly greater for older children in our data, which is similar to the results of other studies [13,16].…”
Section: Risk Factors For Hospitalizationsupporting
confidence: 91%
See 1 more Smart Citation
“…Some studies show no significant difference between males and females [15]. The need for hospital admission was significantly greater for older children in our data, which is similar to the results of other studies [13,16].…”
Section: Risk Factors For Hospitalizationsupporting
confidence: 91%
“…As in other studies [8,11,13] the prevalence of asthma in our study was higher in winter, presumably due to the higher frequency of upper respiratory tract infections, which are an important precipitating factor in childhood asthma.…”
Section: Risk Factors For Hospitalizationsupporting
confidence: 85%
“…Study of Harju T et al found that the prevalence of asthma was higherin preschool ages. 11 In the previous study in Tehran (1995), the prevalence of asthma was higher in pre-high school, similar to present study.…”
Section: Discussionsupporting
confidence: 92%
“…[1][2][3][4][5][6][7][8][9] The underlying mechanisms for this autumnal epidemic of asthma morbidity are thought to include some combination of infectious, allergic, environmental, and climatic stimuli. 2,3 More specifically, environmental allergens, viral respiratory infections, exercise, environmental pollutants, tobacco smoke, and emotional stress may contribute to asthma exacerbations.…”
mentioning
confidence: 99%